2004
DOI: 10.1007/s00425-003-1134-0
|View full text |Cite
|
Sign up to set email alerts
|

Cotton-fiber germin-like protein. II: Immunolocalization, purification, and functional analysis

Abstract: Cotton (Gossypium hirsutum L.) contains a germin-like protein (GLP), GhGLP1, that shows tissue-specific accumulation in fiber. The fiber GLP is an oligomeric, glycosylated protein with a subunit size of approximately 25.5 kDa. Accumulation of GhGLP1 occurs during the period of fiber elongation [4-14 days post-anthesis (DPA)]. During early phases of fiber development (2-4 DPA), GhGLP1 localizes to cytoplasmic vesicles as shown by confocal immunofluorescent microscopy. In slightly older fibers (7-10 DPA), GhGLP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 63 publications
2
20
0
Order By: Relevance
“…In a detailed study of the in planta role of OXO in Lolium perenne, Le Deunff et al (2004) concluded that germin OXOs might be instrumental during critical events in the life of plants, such as cutting and senescence by initiating H 2 O 2 -mediated defenses against pathogens and foraging animals. Other mechanisms such as reinforcement of cell walls by GLPs have also been suggested (Lane, 1994;Christensen et al, 2000;Kim et al, 2004). The evidence of possible promoter induction by wounding in the present study may also strengthen the hypothesis that GLPs play an important role in generalized plant defense (Schafleitner and Wilhelm, 2002;Segarra et al, 2003).…”
Section: Resultssupporting
confidence: 87%
“…In a detailed study of the in planta role of OXO in Lolium perenne, Le Deunff et al (2004) concluded that germin OXOs might be instrumental during critical events in the life of plants, such as cutting and senescence by initiating H 2 O 2 -mediated defenses against pathogens and foraging animals. Other mechanisms such as reinforcement of cell walls by GLPs have also been suggested (Lane, 1994;Christensen et al, 2000;Kim et al, 2004). The evidence of possible promoter induction by wounding in the present study may also strengthen the hypothesis that GLPs play an important role in generalized plant defense (Schafleitner and Wilhelm, 2002;Segarra et al, 2003).…”
Section: Resultssupporting
confidence: 87%
“…The absence of any OXO activity in leaves, stems, and roots of the transgenic tobacco overexpressing OsRGLP1 is in accordance with a previous finding (Kim et al 2004) concerning another GLP. Similarly, a GLP isolated from cells of Barbula unguiculata is connected with MnSOD activity but not with OXO activity (Yamahara et al 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Collectively, these results demonstrate that sequence similarity is insufficient evidence to predict accurately how GLPs function in plant cells. Purification and characterization of the GhGLP1 protein is the next step for establishing how this gene product functions in elongating cotton fibers (Kim et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, this proposal is questionable because several groups have been unable to show Mn-SOD activity in their purified germin preparations (Carter and Thornburg 2000;Bernier and Berna 2001;Whittaker and Whittaker 2002;Kim et al 2003;S. Bornemann, personal communication;B.G.…”
Section: Ghglp1 Is Similar To Germins Glps and Abpsmentioning
confidence: 99%
See 1 more Smart Citation